Faktor-Faktor yang Mempengaruhi Implementasi Kebijakan Pelindungan Pekerja Migran Indonesia dalam Mencegah Migrasi Nonprosedural di Kabupaten Ende - Helenerius Ajo Leda; Dominikus Rangga Hayon; Ronaldo Alexander Meze (Yayasan Literasi Sains Indonesia, 2025)
This study was motivated by the high number of cases of non-procedural migration in Ende Regency. The government's efforts to implement migrant worker protection policies are still not optimal. Most previous studies have focused more on internal factors within the government, implementing agencies, and recruitment companies, thus tending to discuss administrative and institutional obstacles. This study seeks to broaden the scope of the research by emphasising the role of external factors, such as the socio-economic conditions of families, kinship networks, and the cultural tradition of migration, which also determine the dynamics of policy implementation. The method used is an exploratory qualitative approach with data collection techniques through in-depth interviews, observation, and documentation analysis, as well as validation through triangulation. The research subjects included local government officials, BP3MI, the police, village/sub-district heads, NGOs, social organisations, former migrant workers, and migrant workers' families. The results show that the implementation of migrant protection policies in Ende Regency is influenced by a combination of external factors, such as household economic conditions, wage differences, kinship culture, and social migration networks, as well as internal factors, such as weak institutional coordination, budget constraints, and the absence of specific regulations. These findings confirm that preventing non-procedural migration requires policy transformation, institutional strengthening, and socio-economic empowerment of the community in order to make migration management safer and more dignified.